Optimizing Passenger Satisfaction in Public Transportation: The Role of Service Innovation and Accessibility - Muhammad Syarif Hidayatullah Elmas; Mila Diana Sari; Ikhwanul Hakim (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to analyze the mediation of trust on the influence of innovation and accessibility on the satisfaction of DAOP IX economy class railway service passenger. Research Methodology: This study aimed to analyze how trust bridges the influence of innovation and accessibility on the satisfaction of DAOP IX economy class train passengers. Using a quantitative approach with 108 respondents, the data were processed through descriptive analysis and Structural Equation Modelling (SEM) using AMOS software. Results: Based on SEM analysis using AMOS software, this research model met the criteria for a good goodness of fit. All hypotheses were answered and proven with significance values below 0.05, both directly and indirectly. These results support the satisfaction theory proposed by the experts. Conclusions: This study proves that trust is the key that transforms innovation and accessibility into passenger satisfaction in the DAOP IX region. PT KAI's digital transformation not only facilitates travel but also builds public trust that underpins service satisfaction profoundly. Limitations: This research has limitations in terms of the minimum sample size of 108 respondents and the narrow coverage area of DAOP IX, making it difficult to generalize the results. In addition, data collection was limited to the year-end holiday period, and the variables focused only on innovation, accessibility, trust, and passenger satisfaction. Contributions: This research provides a theoretical contribution to the development of satisfaction and service marketing management, particularly in strengthening the mediation model of trust that links technical (innovation) and operational aspects with passenger satisfaction in trains.